Workplace Spirituality and Pro-Environmental Behavior: The Role of Employee Engagement and Environmental Awareness (Global Journal of Management and Business Research, 2018)
A key challenge facing organizations is how to encourage employees to engage in proenvironmental behaviors. Workplace spirituality has been conceptualized as offering new insights into how individuals experience a deeper level of intrinsic work motivation and engagement. Based on a survey of 349 nurses, we found that workplace spirituality was significantly associated with nurses' pro-environmental behavior and that employee engagement indirectly affects the relationship between workplace spirituality and pro-environmental behavior. The results suggest that environmental awareness moderated the effect of workplace spirituality on pro-environmental behavior of nurses. Managers of nursing services should consider workplace spirituality and its positive influence on nurses' outcomes in order to improve their performance and, subsequently, the healthcare system.
Keywords: Workplace spirituality; employee engagement; pro-environmental behavior; environmental awareness; nurses